Bargaining in vertical relationships and suppliers' R&D profitability - Christian Köhler (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2014)
This paper explores the effect of bargaining in vertical relationships on the profitability of suppliers' R&D investments. Studies on the relationship between R&D and firm profitability mostly concentrate on the impact of horizontal market structure and neglect vertical interac-tions. Building on theoretical and empirical evidence about the effects of bargaining in vertical relationships, the crucial determinants of a supplier's bargaining power are identified as the market position and the degree of concentration in the buyer portfolio. With respect to R&D profitability the latter is expected to diminish returns from R&D, while the former is expected to increase it. The hypotheses are tested using a sample of 472 German manufactur-ing firms. The empirical findings support all hypotheses and highlight the importance of tak-ing a supplier's bargaining power into account when estimating R&D profitability. The esti-mated effects are considerable: for an average R&D performing supplier an increase of R&D intensity in 2010 by a percentage point would reduce profits by about 14 % in 2012 given the supplier depends completely on the largest three buyers and does hold an average market share. Contrastingly, a monopolist R&D performing supplier with average buyer concentra-tion would experience a profit increase by 10 % in 2012.
urn:nbn:de:bsz:180-madoc-373083
Keywords: D22; L22; O32; 330; Bargaining; Firm performance; Vertical relationships